Germany's Benefit from the Greek Crisis - Geraldine Dany; Reint E. Gropp; Helge Littke; Gregor von Schweinitz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
This note shows that the German public sector balance benefited significantly from the European/Greek debt crisis, because of lower interest payments on public sector debt. This is due to two effects: One, in crisis times investors disproportionately seek out safe investments (“flight to safety“), bidding down the returns on safe-haven assets. We show that German bunds strongly benefited from this effect during the Greek debt crisis. Second, while the European Central Bank (ECB) monetary policy stance was quite close to an “optimal“ monetary policy stance for Germany from 1999 to 2007, during the crisis monetary policy was too accommodating from a German perspective, due to the emerging disparities across the Euro area. As a result of these two effects, our calculations suggest that the German sovereign saved more than 100 billion Euros in interest expenses between 2010 and mid-2015. That is, Germany benefited from the Greek crisis even in case that Greece defaults on all its debt (a total of 90 billions) owed to the German government via diverse channels (European Stability Mechanism [ESM], International Monetary Fund [IMF], or directly).
urn:nbn:de:gbv:3:2-48497
Keywords: 330; European Union; Greek crisis; government bonds; German public budget; Greece; Germany